ED I-PASS: A Streamlined Version of the I-PASS Patient Handoff Tool for the Emergency Department - Sarah R. Williams; Jeffrey Chien; Ryan Ribeira (Journal of Education and Teaching in Emergency Medicine, 2017)
Audience: The target audience for this presentation includes attendings, residents, advanced practice providers, and medical students who work in the emergency department (ED).